Impact of the crural diaphragm thickness on pulmonary function after lobectomy. (June 2019) - Ota, Hideki; Matsumoto, Hidekazu
Objective: The crural diaphragm is responsible for pulmonary ventilation in the early period after lobectomy. However, the role of its thickness in pulmonary ventilation remains unclear. We investigated the impact of crural diaphragm thickness on pulmonary oxygenation and gas exchange early after lobectomy. Methods: We enrolled 32 patients with non-small-cell lung cancer who underwent video-assisted thoracoscopic lobectomy. Crural diaphragm thickness was defined as the average of the maximum thicknesses of the right and left crural diaphragm at the level of the median arcuate ligament on computed tomography. Pulmonary oxygenation and gas exchange were evaluated by the ratio of arterial oxygen tension/fraction of inspiratory oxygen and alveolar-arterial oxygen difference on the second postoperative day. Results: Crural diaphragm thickness of 7.0 ± 1.7 mm was associated with vital capacity. After lobectomy, arterial oxygen tension/fraction of inspiratory oxygen decreased significantly and alveolar-arterial oxygen difference increased significantly. Five patients with oxygen saturation via pulse oximetry ≤92% had a lower arterial oxygen tension/fraction of inspiratory oxygen and higher alveolar-arterial oxygen difference than the others. Crural diaphragm thickness in these patients was less than in the others (5.5 ± 1.9 vs. 7.3 ± 1.5 mm, p  = 0.033). In multivariate analysis, crural diaphragm thickness remained an independent factor affecting arterial oxygen tension/fraction of inspiratory oxygen and alveolar-arterial oxygen difference ( p  = 0.044, p  = 0.049). Crural diaphragm thickness was positively associated with arterial oxygen tension/fraction of inspiratory oxygen and negatively associated with alveolar-arterial oxygen difference. Conclusion: Crural diaphragm thickness affects pulmonary ventilation early after lobectomy.